2018
DOI: 10.1038/s41426-018-0089-y
|View full text |Cite
|
Sign up to set email alerts
|

An epizootic of Chlamydia psittaci equine reproductive loss associated with suspected spillover from native Australian parrots

Abstract: Chlamydia psittaci is an avian pathogen capable of spill-over infections to humans. A parrot C. psittaci strain was recently detected in an equine reproductive loss case associated with a subsequent cluster of human C. psittaci infections. In this study, we screened for C. psittaci in cases of equine reproductive loss reported in regional New South Wales, Australia during the 2016 foaling season. C. psittaci specific-PCR screening of foetal and placental tissue samples from cases of equine abortion (n = 161) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
124
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(139 citation statements)
references
References 37 publications
(70 reference statements)
11
124
3
1
Order By: Relevance
“…Nevertheless, the question remains whether the livestock animals are indeed commonly infected with this pathogen or if C. psittaci detection is a result of environmental exposure. Potential C. psittaci contamination from bird excretions was suggested for the recent C. psittaci horse epizootic (Borel et al, ; Jenkins et al, ). To date, the reports of C. psittaci infections in Australian sheep and cattle were unclear and inconclusive (Seaman, Cockram, & Scrivener, ), in contrast to the global studies recognizing the significant role of C. psittaci in livestock infection and disease (Borel et al, , ; Ostermann et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the question remains whether the livestock animals are indeed commonly infected with this pathogen or if C. psittaci detection is a result of environmental exposure. Potential C. psittaci contamination from bird excretions was suggested for the recent C. psittaci horse epizootic (Borel et al, ; Jenkins et al, ). To date, the reports of C. psittaci infections in Australian sheep and cattle were unclear and inconclusive (Seaman, Cockram, & Scrivener, ), in contrast to the global studies recognizing the significant role of C. psittaci in livestock infection and disease (Borel et al, , ; Ostermann et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…(a) the host range for this species in Australia is broader than previ- (Borel et al, 2018;Jenkins et al, 2018). To date, the reports of C. psittaci infections in Australian sheep and cattle were unclear and inconclusive (Seaman, Cockram, & Scrivener, 1986), in contrast to the global studies recognizing the significant role of C. psittaci in livestock infection and disease (Borel et al, 2018(Borel et al, , 2006Ostermann et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the authors' surprise, in one season, over 20% of cases of equine pregnancy loss and/or foal death were found to be C. psittaci positive suggesting that non-avian animal hosts may be more common than previously thought. 14 Notably, this expansion of the host range of C. psittaci in Australian animals was recently expanded with the detection of DNA of this pathogen in Australian domesticated sheep and cattle. 15 While environmental contamination cannot be excluded in the latter cases, these veterinary studies nevertheless highlight that a history of contact with animals beyond birds should be considered in clinical investigations of patients with psittacosis.…”
Section: The Emergence Of New C Psittaci Zoonotic Infection Reservoirsmentioning
confidence: 99%
“…New reports of unusual presentations of chlamydiosis are not limited to humans. A recent study found that >20% of pregnancy losses and early foal deaths in horses were positive for Chlamydia psittaci [4]. C. psittaci is an avian pathogen that can also cause serious atypical pneumonia in humans, known as psittacosis.…”
mentioning
confidence: 99%